Dural Arteriovenous Fistula Presenting As Pulsatile Tinnitus. Issue 1 (9th November 2021) - Van Sumere, Maxime; Defreyne, Luc; VandeVyver, Vincent
Teaching point : We report magnetic resonance imaging characteristics of a dural arteriovenous fistula (dAVF), a possible cause of pulsatile tinnitus.